Join the Club - On the Attractiveness of Golf Club Membership - Johan Lundberg; Sofia Lundberg (European Regional Science Association (ERSA), 2004)
This paper concerns the attractiveness for member ship in Swedish golf clubs. A representative voter model is derived and the attractiveness for member ship in golf clubs estimated using a unique data set on qualities of the golf course, the quality of neighboring courses and characteristics regarding the region where the golf club is located. Characteristics and composition of population within the municipality where the club is located have a significant impact on the attractiveness of the club. The attractiveness increases as the share of number of junior members decrease. Golf is found to be a substitute to publicly financed goods. Keywords: spatial econometrics, sports, utility maximization JEL classification: D71, L83, R12
Keywords: D71; L83; R12; 330; spatial econometrics; sports; utility maximization